Efektivitas Peregangan Otot untuk Meningkatkan Konsentrasi Belajar pada Mahasiswa Jurusan Psikologi di Universitas Negeri Padang - Sari, Anisa Silvina; Pradhita, Cindi; Ramadhani, Putri; Ramadina, Salsabila; Aulia, Prima (Lembaga Yasin AlSys, 2024)
Decreased concentration on learning can occur due to prolonged sitting, which causes nervous tension. This can be overcome by stretching the muscles. This study aims to determine and analyze the effectiveness of muscle stretching, namely progressive muscle relaxation to increase the concentration of learning students majoring in psychology at Padang State University. The method used is an experiment with a pretest-posttest control group design. The sampling technique is purposive sampling which involves 10 psychology students who have moderate and low concentration scores, then divided into two groups, namely the experimental group (5 people) and the control group (5 people). Data analysis showed that the average test score of the experimental group increased from 73.00 to 79.80, while the control group decreased from 74.40 to 72.60. Normality and homogeneity tests confirmed that the data were normally distributed and homogeneous. Hypothesis testing using independent sample t-test showed a significant difference between the two groups with a significance value of 0.006 (p < 0.05). The conclusion of this study shows that muscle stretching effectively improves students' study concentration, as shown by the significant increase in the mean score of the experimental group compared to the control group.